KONFLIK ORANG CINA DAN PRIBUMI DI BAGANSIAPIAPI TAHUN 1946 - Rohmaini '; Drs. Ridwan Melay, Hum; Drs. Kamaruddin, M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The main problem of life in the era of social plurality is a conflict, either between individuals or groups. Conflict can be called as an enduring entity in any difference. Therefore, there is a difference semasih eliminate it is